Examining International Students’ Attitudinal Learning in a Higher Education Course on Cultural and Language Learning - Watson, William R.; Watson, Sunnie Lee; Fehrman, Sarah E.; Yu, Ji Hyun; Janakiraman, Shamila (Journal of International Students, 2020)
This study examined students’ perceptions of attitudinal learning outcomes and instructional activities within a language and cultural exchange (LACE) course at a midwestern U.S. university and explored whether perceptions differed based on students’ prior knowledge, major, and/or demographics. We utilized a mixed-methods approach to gather quantitative data from a survey sent out in Weeks 5 and 15 to 137 international students enrolled in multiple sections of a LACE course that gathered perceptions on attitudinal learning and the most impactful aspects of the course design. Follow-up structured interviews were conducted with 37 students. Results indicated students saw growth in their attitudinal learning, with the highest perceived gains regarding cognitive and then behavioral components. Data from student interviews provided specific examples of how student attitudes were changed in each of these four areas of learning. Limitations and future research are discussed.